Microorganism-based synthesis of nanomaterials and their applications - Khairatun Najwa, Mohd Amin; Rohana, Abu; Sharifah Fathiyah, Sy Mohamad; Afkar Rabbani Hidayatullah, Hipeni (Wiley, 2024)
The advancement of nanomaterials production has shifted from mechanical and chemical-based synthesis to green synthesis by microorganisms. For the past years, the foundations of microorganism-based synthesis have been laid by scientists to point out the vast potential in terms of reliability and sustainability. This was followed by a demonstration of process enhancement using genetically modified engineering approaches, which contributed to the high yield of desired nanomaterials. Diverse microorganisms, like bacteria and fungi, have been employed and will be discussed in this chapter. This chapter will also highlight the recent development of microorganism-based synthesis of organic materials such as cellulose nanomaterials and inorganic materials like metallic nanomaterials. Different mechanisms for these nanomaterials will also be discussed. Finally, the present work on the potential applications of these microorganism-based synthesis nanomaterials like in medical and advanced manufacturing is also mentioned. © 2024 by John Wiley & Sons, Inc. All rights reserved.